Can we enhance the clinical efficacy of cognitive and psychological approaches to treat substance use disorders through understanding their neurobiological mechanisms?. (November 2022) - Maddern, Xavier J.; Walker, Leigh C.; Campbell, Erin J.; Arunogiri, Shalini; Haber, Paul S.; Morley, Kirsten; Manning, Victoria; Millan, E. Zayra; McNally, Gavan P.; Lubman, Dan I.; Lawrence, Andrew J.
Abstract: Despite decades of research in the field of addiction, relapse rates for substance use disorders remain high. Consequently, there has been growing focus on providing evidence-based treatments for substance use disorders, resulting in the increased development and use of cognitive and psychological interventions. Such treatment approaches, including contingency management, community-reinforcement approach, and cognitive bias modification, have shown promising clinical efficacy in reducing substance use and promoting abstinence during treatment. However, these interventions are still somewhat limited in achieving sustained periods of abstinence post-treatment. The neurobiological mechanisms underpinning these treatment approaches remain largely unknown and under-studied, in part, due to a lack of translational animal models. The adoption of a reverse translational approach may assist in development of more representative models that can facilitate elucidation of the mechanisms behind these clinically relevant interventions. This review examines our current understanding of addiction neurobiology from clinical, preclinical research and existing animal models, and considers how the efficacy of such behavioral-oriented interventions alone, or in combination with pharmacotherapy, may be enhanced to improve treatment outcomes. Highlights: We explore contingency management, community-reinforcement and cognitive bias. We examine the known underlying neurobiology behind these approaches. We canvas translationally relevant models to further probe their mechanisms. We posit such models may ultimately help improve treatment outcomes.